BURDEN OF FAMILY CAREGIVERS OF CANCER PATIENTS IN PALLIATIVE CARE - Vale, Jamil Michel Miranda do; Santana, Mary Elizabeth de; Lima, Vera Lúcia de Azevedo; Parente, Andressa Tavares; Sonobe, Helena Megumi; Ferreira, Ilma Pastana (Cogitare Enfermagem, 2023)
Objective: To analyze the correlation between the burden of family caregivers of cancer patients in Palliative Care and the variables gender, age, health problems, and length of care. Method: Descriptive correlational study with a non-probabilistic sample of 147 family caregivers at the Oncological Palliative Care Clinic in 2021 in Belém do Pará - Brazil. The Zarit Overload Scale was used to collect data, with descriptive and inferential statistical analysis. Results: 86 (58.5%) of the caregivers were female, 66 (44.9%) caregivers felt "Very overloaded", and 104 (70.7%) had Moderate to Severe overload. There was no consistency in concluding that the variables gender, age group, health problems, or length of care had a statistically significant relationship (p>0.05). Conclusion: It is hoped that the results will contribute to increasing knowledge of the subject, supporting care practice, and formulating public policies to meet the needs of caregivers of family members who are ill with cancer.